Electrical and photoconducting properties of nanorod in based spinel compound/p-Si photodiode by sol-gel spin coating technique - Tataroglu, A.; Al-Ghamdi, Ahmed A.; Bin Omran, Saad; Farooq, W. A.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Springer, 2014)
A new Schottky diode (InFe2O4/p-Si/Al) was fabricated using the sol-gel spin coating technique. The current-voltage (I-V) characteristics of the Schottky diode were investigated under various illumination intensities. The value of ideality factor (n) and zero-bias barrier height (I broken vertical bar(B0)) for all illuminations was determined by using the forward-bias I-V measurements, and were found to be about 4.20 and 0.72 eV, respectively. The reverse current of the diode in the reverse bias increases with the increasing illumination intensities. Also, the photocurrent under illumination is higher than the dark current. In addition, the capacitance-voltage (C-V) and conductance-voltage (G-V) measurements of the diode were studied in the frequency range of 10 kHz-1 MHz. The measured values of the C decrease with the increasing frequency. The decrease in capacitance was explained on the basis of interface states. To obtain the real C and G of the diode, the measured values of C and G were corrected to eliminate the effect of series resistance. The obtained results suggest that the diode can be used as a photodiode in optoelectronic applications.
Keywords: Schottky diode; Sol gel; Spinel compound; Interface states; Series resistance